Seafloor structural observations, Costa Rica accretionary prism - McAdoo, Brian G. (1996)
By studying seafloor morphology we can make associations between near surface defornation, fluid flow and the overakk structural framework of accretionary prisms. In February, 1994 a DS/RV ALVIN program to the Costa Rica accretionary prism investigated the relationship of fluid seepage and sediment deformation by using the distribution of chemosynthetic communities and heat flow anormalies as indicators of fluid flow. The active normal faults that cut the hemipelagic section on the Cocos plate may provide conduits for fluids that cause the regional heat flow to be extremely low. These normal faults intersect the toe of the prism at an oblique angle, creating localized regions of increased deformation. Positive heat flow anormalies observed at the deformation. Positive heat flow anormalies observed at the deformation front indicate of flow, however, we discovered ni seep communities indicative of focused flow. The seaward-most seep communities discovered are in a region of active out-of-sequence thrusts that cut a sediment apron which covers the complex to within 3 km of the prism toe. Vents occur consistently at the base of the fault scarps. Dives in a mud diapir show extensive seep communities, pock marks, and authigenic carbonates. Evidence of a fluid release is on the crest which implies a low viscosity fluid migrating upward in the center of the structure. Normal faults on the upper slope can be seen in cross- section in the walls of a submarine canyon. The faults cut the slope apron and displace the seafloor, actively maintaining the critical taper of the prism.